Dwarapala at the Vyankatesh Balaji Temple - Ghosh, Ayan (2023)
Dwarapala holding a mace at the entrance to Vyankatesh Balaji Temple. Due to the asymmetric layout of the temple and lack of wall space at the entrance, only a lone dwarapala stands guard instead of the usual pair.